TV Híradó
interveiw with Gyula Horn in the hospital after his road accident, MDF assembly meeting, reflections on the elections from abroad, Bosnia, Jemen, Israel, State Property Agency, bank consolidation, savings cooperatives, car parking in Budapest, drinking water in Pécs, Day of Birds and Trees, hospital in Debrecen, Munkáspárt, Köztársaság Párt, MIÉP, Magyarországi Szociáldemokrata Párt, reactions abroad, elections news, Strassbourg, Sarajevo, demonstration in front of the Ministry of Labour, Berva, Aeroplex airplane maintenenace company, privatisation of pharmacies, newsreel section "The Day", business friendy local government